Pengaruh Psikologis Pencahayaan Buatan pada Interior Kamar Tidur Anak - Hayatthien, Nirmala Sari; Wardhana, Sakundria Satya Murti (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Lighting and color in interior design have a significant influence on the psychology of individuals, especially in children's bedroom spaces. This study aims to identify appropriate lighting colors and understand their effects on children's health and psychology. This research uses qualitative methods of literature study type, by reviewing literature from various sources such as journals, articles, and studies related to lighting, color, and psychology. The research stages include searching for relevant types of literature, reading, reviewing, and presenting the results of literature studies. The results of this study suggest that the color of lighting in children's bedrooms can affect their mood and well-being. Red and yellow colors, when used with low intensity, are suitable for creating a warm and comfortable atmosphere, as well as helping to increase the production of the hormone melatonin, which contributes to better sleep and improves children's mood and mental health. In the context of children's bedroom interior design, the selection of the right lighting colors is essential to create an environment that supports their psychological development and well-being